Penggunaan Metode Mind Mapping Pada Mata Pelajaran IPAS Kelas IV SD Negeri 057228 - Astri Riahma Br Saragih; Rahimul Harahap (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2026)
This study aims to determine the effect of using the Mind Mapping technique on students' learning outcomes in the subject of Natural and Social Sciences (IPAS) in the fourth grade of SD Negeri 057228 Petani Jaya. The background of this study is the low student learning outcomes, which are still below the Minimum Mastery Criteria (KKM), as well as the dominance of conventional teaching methods that lack active student involvement.This study uses a quantitative approach with an experimental design. The fourth-grade students were divided into two groups: an experimental class and a control class. Data were collected through learning outcome tests, observations, and documentation, and then analyzed using statistical tests to determine the differences between the two groups.The results of the study show that the Mind Mapping method has a significant effect on improving students' learning outcomes. Students who were taught using this method achieved better results compared to those who were taught using conventional methods. In addition, the Mind Mapping method can increase students' activeness, creativity, and understanding of the learning material.Thus, it can be concluded that the Mind Mapping method is effective in improving students' learning outcomes in the IPAS subject. Keywords: Mind Mapping, learning outcomes, IPAS, elementary school